The distress of Marks & Spencer PLC in 2001: A multidimensional scaling analysis - Mar Molinero, Cecilio; Bishop, Hannah; Turner, Michael (Cuadernos de Estudios Empresariales, 2006)
Marks & Spencer PLC, one of the largest retail companies in the UK, went through a difficult period in 2001. Drastic measures were taken to turn the company around. This paper attempts to put the problems of the company within the context of its industry. The methodology used for the study is based on Multidimensional Scaling, a multivariate technique that serves to represent the main features of the data, and brings its most salient aspects to the fore. It was found that Marks & Spencer PLC had been loosing ground with respect to other companies in the same industry. Management action appears to have been related to a loss of confidence on the part of the financial markets.